2015
DOI: 10.1136/bmjopen-2014-006578
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of physician attire on patient perceptions: a systematic review of the literature— targeting attire to improve likelihood of rapport (TAILOR) investigators

Abstract: ObjectivesDespite a growing body of literature, uncertainty regarding the influence of physician dress on patients’ perceptions exists. Therefore, we performed a systematic review to examine the influence of physician attire on patient perceptions including trust, satisfaction and confidence.Setting, participants, interventions and outcomesWe searched MEDLINE, Embase, Biosis Previews and Conference Papers Index. Studies that: (1) involved participants ≥18 years of age; (2) evaluated physician attire; and (3) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
162
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(186 citation statements)
references
References 33 publications
10
162
3
7
Order By: Relevance
“…This study has several limitations. The study was conducted at one institution in an urban setting with relatively young patients, which is a potentially important limitation as previous studies have established the influence of location, culture, and age on patients' preferences [16,22]. For several reasons, location may have an effect on respondents' preferences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has several limitations. The study was conducted at one institution in an urban setting with relatively young patients, which is a potentially important limitation as previous studies have established the influence of location, culture, and age on patients' preferences [16,22]. For several reasons, location may have an effect on respondents' preferences.…”
Section: Discussionmentioning
confidence: 99%
“…For professional and hygienic reasons, the debate has persisted regarding the most appropriate clothing and how this may affect the patient-physician relationship. Numerous studies have confirmed the strong influence of physician attire on communication, patient education, confidence, trust, respect, adherence to medical treatments, and ultimately the quality of care patients receive [6,7,15,22,23]. Although concepts such as trust and confidence are complex and likely involve many other factors such as respect and good communication, previous studies in settings outside orthopaedics have confirmed attire influences these variables [2,12,16,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea that some patient populations prefer doctors in white coats certainly is not new. Others have found that white coats inspire trust [9], that they make doctors easier to identify from among other hospital personnel (although this probably is not a reliable form of identification [3,11]), and that older patients in particular seem to like them [3]. Patient satisfaction is what matters, and this study by Dr. Haydel's team in this month's CORR 1 represents the best orthopaedic-specific information we have on the topic.…”
mentioning
confidence: 83%